2007
DOI: 10.1002/j.1556-6678.2007.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metaphor in Clinical Supervision

Abstract: UThe authors completed a critical review of the literature on the use of metaphor and the efficacy of metaphoric activities in clinical supervision. The authors conclude that these activities might assist students in understanding the process of becoming a counselor and facilitate students' case conceptualization skills. Cautions to consider when implementing metaphoric activities, limitations of research that has investigated the effectiveness of using metaphors in supervision, and suggestions for future rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
1
18
0
3
Order By: Relevance
“…According to the domains and categories, the participants reported that they gained new perspectives through the use of metaphors in the structured peer group supervision process, and they had a progress in their counseling cognitive skills such case conceptualization, therapeutic skills, and intervention skills. These findings are consistent with the previous research findings (Guiffrida et al, 2007;Robert & Kelly, 2010;Young & Borders, 1999). The previous studies indicated that the use of metaphors during the supervision process provides much contribution in terms of understanding clients and developing hypotheses, forming and developing counseling goals, forming alternative treatment methods, and understanding the relationship between client and counselor.…”
Section: Extended Abstractsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the domains and categories, the participants reported that they gained new perspectives through the use of metaphors in the structured peer group supervision process, and they had a progress in their counseling cognitive skills such case conceptualization, therapeutic skills, and intervention skills. These findings are consistent with the previous research findings (Guiffrida et al, 2007;Robert & Kelly, 2010;Young & Borders, 1999). The previous studies indicated that the use of metaphors during the supervision process provides much contribution in terms of understanding clients and developing hypotheses, forming and developing counseling goals, forming alternative treatment methods, and understanding the relationship between client and counselor.…”
Section: Extended Abstractsupporting
confidence: 92%
“…In the supervision literature, there are many metaphoric activities which formulated to be used in supervision process such as metaphoric stories and drawings, sand tray, Greek mythology etc. (Guiffrida et al, 2007). These metaphoric activities were intentionally used in supervision by supervisors.…”
Section: Extended Abstractmentioning
confidence: 99%
“…In addition, with the intentional use of metaphors, supervisors and students become more aware of client-generated metaphorical narratives, facilitating client case conceptualization, therapeutic relationship, and intervention strategies (Robert & Kelly, 2010). However, effective use of metaphor in supervision is likely dependent upon a supervisee's ability to think both abstractly and creatively as well as the supervisor's level of skill and comfort with developing appropriate ways of incorporating these techniques (Guiffrida et al, 2007). Jackson, Muro, Lee, and DeOrnellas (2008) advocated for using mandalas (drawings within circles, considered to be healing) in counseling supervision as a way to increase supervisees' self-awareness and to broaden understanding of complicated cases.…”
Section: Case Conceptualizationmentioning
confidence: 98%
“…Most of the literature about using art-based methods in supervision claims that artmaking in the supervision context leads to supervisees' increased self-awareness(Deaver & McAuliffe, 2009;Guiffrida et al, 2007;Harter, 2007;Jackson et al, 2008;Newsome et al, 2005). For example, all of the participants in Deaver and McAuliffe's study found that visual journaling facilitated insight about themselves and their clients.Guiffrida and collea- gues (2007) asserted that drawing activities in the context of supervision facilitated ''supervisee self-understanding and awareness'' (p. 393).…”
mentioning
confidence: 91%
See 1 more Smart Citation